Computation of stress intensity factors by the compliance approach - Hamoush, Sameer A.; Abdel-Fattah, Hisham (Computer Assisted Methods in Engineering and Science, 2000)
A numerical method based on compliance approach is presented for analyzing an isotropic homogeneous sheet enclosing a crack. The method calculates the strain energy release rate and determines the stress intensity factors KI and KII. This method is suitable for any load combination in pure mode I, pure mode II and mix mode loading. A simple and efficient solution approach is developed in which the strain energy release rate is calculated by combining the finite element method with the fundamental relationships in fracture mechanics. The solution technique converges to accurate results for a small crack extension of the finite element mesh. The solution approach is also shown to be suited for separating the mode I and mode II stress intensity factors for a mixed mode loading. Numerical examples are presented to demonstrate the accuracy of the proposed approach.